High pyocyanin production and non-motility of Pseudomonas aeruginosa isolates are correlated with septic shock or death in bacteremic patients. - Asmita Gupte; Jeevan Jyot; Malleswari Ravi; Reuben Ramphal (PLoS ONE)
Studies of the outcome of Pseudomonas aeruginosa bacteremia (Pab) have focused mainly on antibiotic appropriateness. However, P. aeruginosa possesses many virulence factors whose roles in outcomes have not been examined in humans, except for the type III secretion system (T3SS) toxins. The purpose of this study was to examine the role of virulence factors other than the T3SS toxins. Bacterial isolates were collected from 75 patients who suffered from Pa blood stream infections. Host factors such as neutropenia, immunosuppression, comorbidities, time to effective antibiotics, source of bacteremia, and presence of multidrug resistant (MDR) isolate were studied. The isolates were analyzed for the presence of toxin genes, proteolytic activity, swimming and twitching motility, and pyocyanin production. The data were analyzed to ascertain which virulence factors correlated with poor outcomes defined as septic shock or death (SS) within 7 days. Septic shock or death occurred in 25/75 patients. Univariate analysis identified age as a host factor that exerted a significant effect on these outcomes. Ineffective antibiotics administered during the first 24 hours of treatment or MDR P. aeruginosa did not influence the frequency of SS, nor did the presence of lasB, exoA, exoS exoU, plcH genes and proteolytic activity. However, 6/8 patients infected with non-motile isolates, developed SS, p = 0.014 and 5/6 isolates that produced large amounts of pyocyanin (>18ug/ml), were associated with SS, p = 0.014. Multivariate analysis indicated that the odds ratio (OR) for development of SS with a non-motile isolate was 6.8, with a 95% confidence interval (CI) (1.37, 51.5), p = 0.030 and with high pyocyanin producing isolates, an OR of 16.9, 95% CI = (2.27, 360), p = .017. This study evaluating the role of microbial factors that significantly effect outcomes following Pa bloodstream infection suggests that P. aeruginosa strains showing high pyocyanin production and the lack of motility independently increase the risk of SS.